Sustainable Release of Propranolol Hydrochloride Laden with Biconjugated-Ufasomes Chitosan Hydrogel Attenuates Cisplatin-Induced Sciatic Nerve Damage in In Vitro/In Vivo Evaluation - Yasmin M. Ahmed; Raha Orfali; Doaa S. Hamad; Mostafa E. Rateb; Hanan O. Farouk (MDPI AG, 2022)
Peripheral nerve injuries significantly impact patients' quality of life and poor functional recovery. Chitosan-ufasomes (CTS-UFAs) exhibit biomimetic features, making them a viable choice for developing novel transdermal delivery for neural repair. This study aimed to investigate the role of CTS-UFAs loaded with the propranolol HCl (PRO) as a model drug in enhancing sciatica in cisplatin-induced sciatic nerve damage in rats. Hence, PRO-UFAs were primed, embedding either span 20 or 60 together with oleic acid and cholesterol using a thin-film hydration process based on full factorial design (24). The influence of formulation factors on UFAs' physicochemical characteristics and the optimum formulation selection were investigated using Design-Expert® software. Based on the optimal UFA formulation, PRO-CTS-UFAs were constructed and characterized using transmission electron microscopy, stability studies, and ex vivo permeation. In vivo trials on rats with a sciatic nerve injury tested the efficacy of PRO-CTS-UFA and PRO-UFA transdermal hydrogels, PRO solution, compared to normal rats. Additionally, oxidative stress and specific apoptotic biomarkers were assessed, supported by a sciatic nerve histopathological study. PRO-UFAs and PRO-CTS-UFAs disclosed entrapment efficiency of 82.72 ± 2.33% and 85.32 ± 2.65%, a particle size of 317.22 ± 6.43 and 336.12 ± 4.9 nm, ζ potential of −62.06 ± 0.07 and 65.24 ± 0.10 mV, and accumulatively released 70.95 ± 8.14% and 64.03 ± 1.9% PRO within 6 h, respectively. Moreover, PRO-CTS-UFAs significantly restored sciatic nerve structure, inhibited the cisplatin-dependent increase in peripheral myelin 22 gene expression and MDA levels, and further re-established sciatic nerve GSH and CAT content. Furthermore, they elicited MBP re-expression, BCL-2 mild expression, and inhibited TNF-α expression. Briefly, our findings proposed that CTS-UFAs are promising to enhance PRO transdermal delivery to manage sciatic nerve damage.